Eksistensi dan Efektivitas Surat Edaran Larangan Kangkang - Amrizal J. Prang (Media Syari'ah, 2012)
The Goverment’s policy or the state administration officials regulation in The City of Lhokseumawe, Aceh, and its as part of a regulatory authority policy (Vrije Bevoegdheid) in government to act, based on the principle of freies ermessen or discretion. In the implementation of the government rules, this policy as a part of the operational implementation and that can not change or deviate the legislation. In fact, this policy has not been affectively implemented in the community, due to its implementation complied by most people of Lhokseumawe, whether they are compliance, identification, or Internalization.